Living Values in School: The Implementation of Pancasila and Islamic Moderation Profiles in Early Education - Ulpah Maspupah; Suparjo (Interdisciplinary Journal of Social Science and Education (IJSSE), 2025)
This study investigates the implementation of the Pancasila Student Profile (P5) and Rahmatan Lil Alamin Student Profile (PPRA) at MI Ma’arif NU Ciberem, an Islamic primary school in Central Java, Indonesia. Using a qualitative descriptive method, data were collected through semi-structured interviews with school leaders and teachers, supported by observations and documentation. The findings show that the school integrated P5 and PPRA values into project-based learning activities such as gardening, creative recycling, and local culinary projects. These activities promoted collaboration, environmental awareness, creativity, and spiritual growth in students. Despite challenges such as limited infrastructure and low parental involvement, the school successfully internalized national and religious values into its curriculum and culture. The study concludes that integrating P5 and PPRA can foster holistic character development in early education and offers a practical model for Islamic schools implementing value-based learning.